The Effect Of Consumer Trust And Service Performance On Customer Loyalty Of PT. JNE - Thomas Aquinas Radito; Jefrisom Jefrison; Meniek Srining Prapti (Journal of Management and Business Environment (JMBE), 2023)
PT. Tiki Jalur Nugraha Ekakurir (JNE) was ranked at the top among freight forwarding companies during 2020–2022. Its ability to attract more customers than its competitors indicates the company is able to maintain and improve customer loyalty. This study aims to know if customer loyalty is significanly influenced by consumer trust and service performance. The study conducted in Indonesia addressed 150 JNE customers as the sample. They were selected using purposive sampling and the data collected from them through questionnaire distributed in the form of google-form. The results support this although their ability to explain the variety of customer loyalty, as indicated by R square, is low. However, the model test (F test) confirms that the regression model of this study is able to explain the phenomena relatively well